Sex-specific trajectories of ADHD symptoms from adolescence to young adulthood - Millenet, Sabina; Laucht, Manfred; Hohm, Erika; Jennen-Steinmetz, Christine; Hohmann, Sarah; Schmidt, Martin H.; Esser, Günter; Banaschewski, Tobias; Brandeis, Daniel; Zohsel, Katrin (European child & adolescent psychiatry, 2018)
Reports of current ADHD symptoms in adults with a childhood diagnosis of ADHD are often discrepant: While one subgroup reports a particularly high level of current ADHD symptoms, another reports-in contrast-a very low level. The reasons for this difference remain unclear. Although sex might play a moderating role, it has not yet been examined in this regard. In an epidemiological cohort study from birth to young adulthood, childhood ADHD diagnoses were assessed at the ages of 4.5, 8, and 11 years based on parent ratings. Sex-specific development of ADHD symptoms was analyzed from the age of 15 to 25 years via self-reported ADHD symptoms in participants with (n = 47) and without childhood ADHD (n = 289) using a random coefficient regression model. The congruence between parent reports and adolescents' self-ratings was examined, and the role of childhood ADHD diagnosis, childhood OCC/CD, and childhood internalizing disorder as possible sex-specific predictors of self-reported ADHD symptoms at age 25 years was investigated. With regard to self-reported ADHD symptoms, females with a childhood ADHD diagnosis reported significantly more ADHD symptoms compared to females without childhood ADHD and males with and without ADHD throughout adolescence and young adulthood. In contrast, males with childhood ADHD did not differ from control males either at age 15 or at age 25 years. Only in females did a childhood diagnosis of an externalizing disorder (ADHD and CD/ODD) predict self-reported ADHD symptoms by age 25 years. Our findings suggest that self-reports of young adults with a childhood diagnosis of ADHD are influenced by sex. Specifically, females with childhood ADHD report increased levels of ADHD symptoms upon reaching adulthood. To correctly evaluate symptoms and impairment in this subgroup, other, more objective, sources of information may be advisable, such as neurophysiological measures.
Gesehen am 20.04.2020